Record of affiliated organisations with membership, affiliated fees, by-election fund payments, secretaries and delegates, London, 1941. - Labour Party (London : Labour Party, 1941)
Bibliotheek Camille Huysmans
Engels
Monografie
Keywords: Labour Party; Wereldoorlog 2; vakbonden; socialistische verenigingen; Groot-Brittannië.